KONSEP DASAR IPA BERBASIS STEM PJBL PADA KETERCAPAIAN DOMAIN AFEKTIF MAHASISWA PGMI STIT SUNAN GIRI BIMA - Prihatin, Relly (Fashluna: Jurnal Pendidikan Dasar dan Keguruan, 2020)
This study aims to describe the effect of learning the basic concepts of science-based STEM in the affective domain on student achievement of PGMI. STEM-based education is a new education concept. STEM is not only have meaning as strengthening educational praxis in fields of STEM separately, but rather to develop an educational approach to the problems solving in daily life, and also about attitude, motivation, responsibility for the task, collaboration, etc. Affective Domain is an important domain that should be raised because they relate to the experiences of learners in the learning environment. Method of this study uses a qualitative approach with classroom action research (CAR). The results of the study in the first cycle resulted the scores for each stage was 80% in average with students’ lowest score of 60 and 45. In the second cycle score increases become very good about 90% with students’ highest score was 85 and the lowest score was 75.